Molecular Dynamics Simulations of Mitochondrial Uncoupling Protein 2 - Škulj, Sanja; Brkljača, Zlatko; Kreiter, Jürgen; Pohl, Elena E; Vazdar, Mario (International journal of molecular sciences, 2021)
Molecular dynamics (MD) simulations of uncoupling proteins (UCP), a class of transmembrane proteins relevant for proton transport across inner mitochondrial membranes, represent a complicated task due to the lack of available structural data. In this work, we use a combination of homology modelling and subsequent microsecond molecular dynamics simulations of UCP2 in the DOPC phospholipid bilayer, starting from the structure of the mitochondrial ATP/ADP carrier (ANT) as a template. We show that this protocol leads to a structure that is impermeable to water, in contrast to MD simulations of UCP2 structures based on the experimental NMR structure. We also show that ATP binding in the UCP2 cavity is tight in the homology modelled structure of UCP2 in agreement with experimental observations. Finally, we corroborate our results with conductance measurements in model membranes, which further suggest that the UCP2 structure modeled from ANT protein possesses additional key functional elements, such as a fatty acid-binding site at the R60 region of the protein, directly related to the proton transport mechanism across inner mitochondrial membranes.
Keywords: Protein Binding; Protein Stability; adenosintrifosfát; simulace molekulární dynamiky; stabilita proteinů; Structure-Activity Relationship; mastné kyseliny; membránové proteiny; purine nucleotide; Membrane Proteins; Molecular Dynamics Simulation; Amino Acid Sequence; Uncoupling Protein 2; Fatty Acids; mitochondriální proteiny; membrane protein; iontový transport; vztahy mezi strukturou a aktivitou; Mitochondrial Proteins; vazba proteinů; long-chain fatty acid; Animals; Ion Transport; konformace proteinů; zvířata; uncoupling; conductance measurements in model membranes; sekvence aminokyselin; myši; Adenosine Triphosphate; Protein Conformation; Mice; proton transfer; uncoupling protein 2